Mechanical behavior of dented steel pipes subjected to bending and pressure loading - Pournara A.E., Papatheocharis T., Karamanos S.A., Perdikaris P.C. (Journal of Offshore Mechanics and Arctic Engineering, 2019)
The presence of dents on steel pipeline wall may constitute a threat for pipeline structural safety. Experimental testing results supported by numerical simulations are reported, in an attempt to assess the structural integrity of smoothly dented (nongauged) steel pipes. Ten experiments on 6 in diameter X52 steel pipes are reported, where dented steel pipes are subjected to bending and pressure loading, in order to estimate their residual strength and remaining fatigue life. Six specimens were subjected to cyclic bending loading, whereas four dented pipe specimens, following cyclic pressure loading, have been pressurized to burst to determine their ultimate pressure capacity. Numerical simulation of the testing procedure and, in particular, the loading pattern of each specimen (denting and cyclic loading) has also been performed so that local stress and strain distributions at the dented region are calculated accurately. Based on the finite element results, a simple and efficient fatigue assessment methodology is adopted, to estimate the remaining fatigue life and the predictions were found to compare with the experimental results. Finally, following a parametric numerical study, strain concentration factors (SNCFs) for dented pipes subjected to bending are calculated, to be used in fatigue life assessment. © 2019 by ASME.